CONVERSATIONAL IMPLICATURE IN A DRAMA SCRIPT BY SID RIVER - Dwi Iswahyuni (Jurnal Bahasa Lingua Scientia, 2019)
The characters in a drama sometimes say implicitly so that what are said are different from what are meant. This study investigates conversational implicature in a drama script entitled “Sherlock Holmes and the Mystery of the Aquilla” by Sid River. The aim of the study was to find out what conversational maxims flouted to generate conversational implicature in the Sid River’s drama script entitled “Sherlock Holmes and the Mystery of the Aquilla” were. The research design employed in this study was a descriptive qualitative research using Grice’s theory. The results of the study showed that from 35 excerpts, 11 excerpts belonged to observing the maxims, and the other 24 excerpts belonged to non-observance of the maxims, especially flouting the maxims. The number of flouting the maxims of Quantity, Quality, Relation, and Manner respectively were 6, 20, 3, 3. Based on the analysis, it can be concluded that the conversational maxims flouted in this drama script are maxims of Quantity, Quality, Relation, and Manner. Moreover, flouting the maxim of Quality mostly occurs while the least occurance is flouting the maxims of Relation and Manner. In other words, the characters in this drama script often say untruthful utterances.